Elevated blood levels of liver-expressed antimicrobial peptide 2 in patients with insulinoma and its expression in insulinomas - Zhang, Jia-Lei; Tong, An-Li; Feng, Yun-Lu; Zhao, Da-Chun; Zhong, Ling; Gao, Yin-Jie; Song, Yu-Li; Zhang, Tai-Ping; Li, Ming; Chen, Yuan-Jia (Frontiers in Endocrinology, 2025)
ObjectiveMost patients with insulinoma are overweight or obese. Ghrelin levels in insulinoma have been linked to both obesity and hyperinsulinemia. Liver-expressed antimicrobial peptide 2 (LEAP2), a novel hormone and endogenous antagonist of the ghrelin receptor, is associated with obesity; however, its relationship with obesity and hyperinsulinemia in insulinoma, and its expression within tumor tissue, remains unknown.MethodsSerum LEAP2, insulin, and ghrelin levels were measured by ELISA in patients with insulinoma and in age-, sex-, and BMI-matched controls. LEAP2 expression was examined in insulinoma tissue and paired adjacent pancreatic specimens by immunohistochemical staining.ResultsSerum LEAP2 levels were significantly higher in patients with insulinoma than in controls (P = 0.028) and positively correlated with serum insulin levels (r = 0.408, P < 0.001) while negatively correlated with ghrelin levels (r = −0.551, P < 0.01). In controls, serum LEAP2 levels were significantly associated with BMI (P = 0.047), whereas in patients, the correlation did not reach statistical significance (P = 0.067). Immunostaining showed that LEAP2 peptide was expressed in insulinoma tissue.ConclusionSerum LEAP2 levels are elevated in insulinoma and correlate with hyperinsulinemia and BMI. LEAP2 is expressed in insulinoma tissue, suggesting a potential role in the metabolic profile of these patients.